Study on Influence of Spalling Fault Evolution on Meshing Stiffness of Spur Gear - Peng Dai; Jianping Wang; Shuping Yan; Shengzhou Huang; Jun Liu; Fengtao Wang (Jixie chuandong)
As a key transmission mechanism in mechanical equipment，in the meshing transmission process of involute spur gears，under the influence of extreme working conditions，the tooth surface is easy to cause spalling defects，change the meshing rigidity of gear pairs，and seriously affect its working performance and transmission efficiency. On tooth surface spalling morphology evolution process of the gear pair meshing stiffness，to expand the edge line with the original rectangular flake edge line Angle peel fault evolution，combined with the method of potential energy building containing flaking fault gears meshing stiffness calculation model. The results show that when the gear tooth surface spalling occurs，will make the spalling is involved in the meshing range of mesh stiffness is reduced，and with the increase of scaling parameters，small gear meshing stiffness increase trend，and when the peeling area along the axial center gear pair，the surface is asymmetric gear torsional deformation and torsional stiffness. At the same time，due to the existence of friction，the edge of the spalling area will be further expanded，so that the width of the spalling area will increase，resulting in the range of time-varying mesh stiffness curve changes of the gear pair.